Surgical Techniques for the Management of Midcarpal Instability - Ming, Bryan W.; Niacaris, Timothy; Lichtman, David M. (Journal of Wrist Surgery, 2014)
Palmar midcarpal instability (PMCI) is an uncommon and poorly understood disorder. Its etiology is believed to be due to traumatic or congenital laxity of the ligaments (volar and dorsal) that stabilize the proximal row. This laxity results in hypermobility of the proximal carpal row and unphysiologic coupling of the midcarpal joint. Clinically, the condition is manifested by a painful clunk with ulnar and radial wrist deviation. The purpose of this article is to chronicle our personal experience with this condition and to review our current treatment recommendations and outcomes.
Keywords: midcarpal joint; instability; carpus; wrist; radiocarpal ligament